Periodismo investigativo en la formación integral de profesionales en el área de comunicación de la Universidad Técnica de Babahoyo Extensión Quevedo, séptimo semestre año 2020 - Moreira Cedeño, Katherin Andrea (2021)
The title of this research is investigative journalism in the comprehensive training of professionals in the communication area of the technical university of Babahoyo, Quevedo extension, seventh semester of 2020, in which the advantages of the application of investigative journalism over training are highlighted. integral of the students of the communication career, since it is known that this has a practical development that is quite beneficial for those who develop it. The research is carried out by solving a survey of 6 strategic questions delivered to the group of students of the seventh semester of the communication career, in which it is known that the respondents agree that the insertion and development of investigative journalism would help to their training and learning. For this reason, this project seeks to contribute to the insertion of this subject in the training of communication students at the Technical University of Babahoyo.